2010
DOI: 10.1016/j.whi.2009.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Physical Activity and Motivational Interviewing Among Rural African-American Women with Type 2 Diabetes

Abstract: Purpose Motivational interviewing (MI), a patient-centered behavioral counseling style, is a common behavioral intervention strategy. Since intervention outcomes are highly dependent on patient responsiveness to intervention strategy, we evaluated MI perceptions among rural African American women with Type 2 diabetes prior to a physical activity intervention. Methods Four moderator-led focus groups were conducted with patients age 21–50 who had never participated in a MI intervention and who receive diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 26 publications
(27 reference statements)
6
40
0
1
Order By: Relevance
“…This is consistent with a national population-based survey that assessed public preferences regarding participation in clinical decision making that revealed African Americans had a significantly greater preference for leaving decisions to their doctor 27 and a study of communication style preferences of rural African American women with Type 2 diabetes that found MI to be perceived as too patient centered. 9, 28 One meta-analysis of MI interventions also found that having a higher proportion of African American participants was negatively associated with outcomes. 9 …”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a national population-based survey that assessed public preferences regarding participation in clinical decision making that revealed African Americans had a significantly greater preference for leaving decisions to their doctor 27 and a study of communication style preferences of rural African American women with Type 2 diabetes that found MI to be perceived as too patient centered. 9, 28 One meta-analysis of MI interventions also found that having a higher proportion of African American participants was negatively associated with outcomes. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have identified differences between Blacks and Whites in their decision-making style and counseling preferences (Levinson, Kao, Kuby, & Thisted, 2005;S. Miller, Khensani, & Beech, 2009;S.…”
Section: Discussionmentioning
confidence: 99%
“…Too often, general practitioners fail to use a well-respected screening tool like the PHQ 2/9 inventory for depression. Motivational Interviewing might provide one way for physicians to clear obstacles like cultural competence (Miller et al, 2010). Depression leads to lack of exercise and lack of medication adherence.…”
Section: Introductionmentioning
confidence: 99%